Adoption and profitability of BARI released potato varieties in northern region of Bangladesh - Islam, QMS; Matin, MA; Siddiquee, MSH; Islam, MT (Bangladesh Journal of Agricultural Research, 2018)
The study was conducted in three potato growing areas in nothern districts of Bangladesh namely Rajshahi, Rangpur and Thakurgaon. Data were collected during 2016-17 to assess the level of adoption, profitability, farmers attitude towards the cultivation of BARI released potato varieties and to explore the constraints to potato cultivation. The study revealed that 59% potato areas were covered by BARI Alu-7 variety. The varieties BARI Alu-13, BARI Alu-25 and BARI Alu-8 covered 14%, 14% and 12% of the potato areas respectively. The adoption level of seed rate, gypsum and boron were found high which adoption score were 95, 72 and 71. The level adoption of urea, TSP and MoP were over used which adoption score were 103,138 and 110. The adoption levels of cowdung and zinc sulphate were found medium which adoption score were 50 and 61. Only 37% farmers used potato seeds from their own source. Per hectare total cost of BARI released potato cultivation was Tk. 204003 and variable cost was Tk. 161033. The major share of cost was seed (31%) followed by fertilizer (13%) and land use (11%). Per hectare average yield of potato was 28 ton with gross return Tk. 249819 and gross margin Tk. 88786. The net return of potato cultivation was Tk. 45816 per hectare. The benefit cost ratio was 1.22. Infestation of insect and diseases, non-availability of quality seed, high price of seed and inadequate storage facilities were the major constraints to potato cultivation. Bangladesh J. Agril. Res. 43(2): 309-322, June 2018